In vitro effect of ganoderma lucidum extracts on hematological parameter - Ismail, Che Shuraya Che (2005)
Thrombosis is a pathologic condition that occurs when the body forms arterial or venous blood clots that are excessively large and obstruct blood flow. Heart attack, stroke or pulmonary embolism are examples of conditions when develop in blood vessels which may contribute to various symptoms and complications. Therefore the search for an effective agent that can secure full antithrombotic benefits while minimizing the antihaemostatic outcome should be pursued. In this study, in order to assess the effect of Ganoderma lucidum in inhibition of platelet aggregation, two types of extract were prepared from crude powder of commercially available products of Ganoderma lucidum. Both the two types of extracts were tested for their activities on blood cells in vitro. The effects of this mushroom were tested based on the changes in hematological parameters following the treatment with different doses of water and ethanol extract Ganoderma Jucidum using hematology analyzer (Abbott Celldyn 4000). The test duration for the observation was set for 2 hours and the observation were made every 30 minutes intervals. From this study, the results showed that there were no significant difference of effect between different doses of water and ethanol extracts on MPV. However, there were significant differences of the effect of extracts of Ganoderma lucidum in different concentration on MPV at different time intervals. Antiplatelet aggregation activities by indirect evaluation of changes in blood cells parameters in vitro following the treatment with Ganoderma Jucidum extract may not be fully explored or elucidated by the in vitro study. However, theresults from this preliminary study will assist in establishing the direction of an in vivo study, which will be followed. In order to look at the activities of platelet and the effects on other hematological parameters in vivo, a long-term prospective study should be explored to prove the potential use of Ganoderma lucidum mushroom as a prophylactic agent for prevents arterial thrombosis.